Integrasi Himpunan Dan Al-Qur’an Serta Implementasinya Dalam Pembelajaran Matematika - Ainul Fitri; Rizqiya Hasanah; Sofhia Vabiola; Mia Yolanda Utami Putri; M. Imamuddin (KOLONI, 2023)
Mathematics is also in two positions, namely between the real world and the unseen world so that mathematics which does not exist in the real world has an abstract object and mathematics which is not in the unseen world so that the object is not an "appearance". Bringing objects in the language of mathematics from the real world is called abstraction and realizing mathematics in the real world is called application so that mathematics is abstract and in the language of symbols. Because mathematics exists in two worlds, namely the real (syahadah) and the unseen (ghaibiyah), mathematics is also both "half real and half unseen". To understand the real requires a rationalist, empirical and logical approach. Whereas to understand the unseen requires an intuitive, imaginative and metaphysical approach. According to Iwan (Ahmad septiana, 2022), library research or literature research is an effort by researchers to collect information that is relevant and related to the topic or question being studied. According to (abdussakir, 2017) there are four formulations of integration models offered, including: Mathematics from Al-Qur'an : Mathematics explored or developed in Al-Qur'anMathematics for Al-Qur'an : Mathematics is used to practice Al-Quran Mathematics to Al-Qur'an : Mathematics as a tool to Deepen and convey Al-Qur'an Mathematics with Al - Qur'an : Explaining mathematics in the perspective of Al - Qur'an Based on the literature study that has been carried out, it can be concluded that the set concept has a connection with the Al - Qur'an. This is proven by the discovery of verses in the Qur'an which explain the set, for example in Surah Al – Fathir verse 1, An – Nur verse 45, Al – Fatihah verse 7, Al – Kahf verse 12, Al - Waqi' ah verses 7-10, Al - An'am verses 128, Al – Kahf verses 28, Al – Bayyinah verses 7, At – Thaha verses 6, Al – Bayyinah 6, Al - 'Asr verses 1-3, Al – Kahf verses 50 and others. For this reason, in learning activities in the classroom the teacher is expected to be able to apply learning methods that can demonstrate the integration of the concept of set with the Qur'an to students so that the learning activities carried out do not only teach students mathematical concepts but also teach religious values ​​to students. student. Keywords : Integration, Implementation, Set, Al-Qur’an